PERILAKU KONSUMEN PRODUK KOPI CAFE XPRESSO DI KECAMATAN KOTA KEFAMENANU KABUPATEN TIMOR TENGAH UTARA - Nali, Randi; Sipayung, Boanerges Putra; Joka, Umbu; Pramita, Dira Asri (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Coffee consumption in Indonesia is quite large, this is due to the people's habit that in every activity coffee is the main drink. Coffee consumption in the people of Kefamenanu City is increasing so much that coffee drinks are prioritized when entertaining guests in today's society. This research was conducted at Cafe Xpresso in Kota Kefamenanu District, North Central Timor Regency. The population in this research is the number of residents in North Central Timor Regency as consumers with a total of 239,829 people. The sampling technique in this research used a purposive sampling method of 150 respondents. The objectives of this research are: 1) To find out the factors that influence consumers' decisions in consuming coffee at Cafe Xpresso. 2) To determine the competitiveness of Cafe Xpresso in Kota Kefamenanu District. The data analysis method used is Logistic Regression which is used to analyze coffee consumer decisions and the Boston Consulting Group (BCG) Matrix is ​​used to analyze the level of market growth and relative market share. The results of the research are based on Logistic Regression calculations using SPSS version 22 software data, it is known that the factors that have a significant influence on consumer interest in consuming coffee at Café Xpresso are age, product quality and service quality. Meanwhile, those that do not have a significant influence on consumers' decisions in consuming coffee at Café Xpresso are price, location, place design, taste, menu variations and cleanliness. Based on the results of BCG's analysis, it is known that the 2021 market growth rate is 12.75%, the market share is 3.68 times, and in 2022 the market growth rate is 11.09%, the market share is 1.11 times. So it can be seen that Café Xpresso is in quadrant II (stars) position, which means that Café This research also contains 5 marketing strategies, namely: Product Development, Price, Promotion, Place/Location and Expanding Market Size.